γδ T Cell-Mediated Immunity to Cytomegalovirus Infection - Khairallah, Camille; Déchanet-Merville, Julie; Capone, Myriam (Frontiers in Immunology, 2017)
γδ T lymphocytes are unconventional immune cells, which have both innate- and adaptive-like features allowing them to respond to a wide spectrum of pathogens. For many years, we and others have reported on the role of these cells in the immune response to human cytomegalovirus (HCMV) in transplant patients, pregnant women, neonates, immunodeficient children, and healthy people. Indeed, and as described for CD8+ T cells, CMV infection leaves a specific imprint on the γδ T cell compartment: (i.) driving a long-lasting expansion of oligoclonal γδ T cells in the blood of seropositive individuals, (ii.) inducing their differentiation into effector/memory cells expressing a TEMRA phenotype, and (iii.) enhancing their antiviral effector functions (i.e. cytotoxicity and IFNγ production). Recently, two studies using murine CMV (MCMV) have corroborated and extended these observations. In particular, they have illustrated the ability of adoptively transferred MCMV-induced γδ T cells to protect immune deficient mice against virus-induced death. In vivo, expansion of γδ T cells is associated with the clearance of CMV infection as well as with reduced cancer occurrence or leukemia relapse risk in kidney transplant patients and allogeneic stem cell recipients, respectively. Taken together, all these studies show that γδ T cells are important immune effectors against CMV and cancer, which are life-threatening diseases affecting transplant recipients. The ability of CMV-induced γδ T cells to act independently of other immune cells opens the door to the development of novel cellular immunotherapies that could be particularly beneficial for immunocompromised transplant recipients.